Revista digital sobre el proceso de admisión para las instituciones de educación superior públicas del Ecuador - Eguiguren Pazmiño, Jean Pierre (2016)
The new National Grading and Admission System, since now and on will be called (SNNA), has a communicative product that comes in a printed and digital version in the format of a magazine called “Guía para el Acceso a la Educación Superior, decídete, tu vocación, tu profesión”. This communicative product has been given to the majority of aspirants to public universities in the country, showing layout, emission and reception failures, which have been corroborated through a communicational diagnosis directed by the Social Communication Coordination of the National Grading and Admission System, and applied to a central group of people that came in to the institution asking for information about the registration process in order to take the national education exam. Whit the aim of solving these communicational needs, it is intended to generate a hypermedia communicational product under a digital magazine format which will be set in linear navigation with a simple structure similar to the pages of a traditional book and its communicational design, and methodological, didactic and visual structure, so this will allow to avoid distortions during the message reception process and generate a real feedback communicative process